The Allelic Expression of RNA Editing Gene ADARB1 in Hepatocellular Carcinoma Treated with Transarterial Chemoembolization - Zeng J; Han L; Wang T; Huang L; Zheng Y; Zhang N; Li Z; Yang M (Dove Medical Press, 2023)
Jiajia Zeng,1,* Linyu Han,1,* Teng Wang,1,* Linying Huang,1 Yanxiu Zheng,1 Nasha Zhang,2 Ziqiang Li,3 Ming Yang1 1Shandong Provincial Key Laboratory of Radiation Oncology, Cancer Research Center, Shandong Cancer Hospital and Institute, Shandong First Medical University and Shandong Academy of Medical Sciences, Jinan, People's Republic of China; 2Department of Radiation Oncology, Shandong Cancer Hospital and Institute, Jinan, People's Republic of China; 3Department of General Surgery, The First Affiliated Hospital of Shandong First Medical University & Shandong Provincial Qianfoshan Hospital, Jinan, People's Republic of China*These authors contributed equally to this workCorrespondence: Ming Yang, Shandong Provincial Key Laboratory of Radiation Oncology, Cancer Research Center, Shandong Cancer Hospital and Institute, Jinan, Shandong Province, 250117, People's Republic of China, Tel/Fax +86531-67626536, Email aaryoung@yeah.net Ziqiang Li, Department of General Surgery, The First Affiliated Hospital of Shandong First Medical University & Shandong Provincial Qianfoshan Hospital, Jinan, Shandong Province, 250114, People's Republic of China, Email liziqiang1231@yeah.netIntroduction: Transarterial chemoembolization (TACE) is the commonly used therapy of unresectable hepatocellular carcinoma (HCC), though the prognosis of different TACE-treated HCC patients varies, which may be due to the heterogeneity of HCC tumors caused by genetic variants and epigenetic changes such as RNA editing. There is dysregulated RNA adenosine-to-inosine (A-to-I) editing in HCC and RNA-edited genes are involved in the epigenetic process. It remains unclear how genetic variants of RNA editing genes affect the prognosis of HCC cases treated by TACE.Methods: In this study, we examined 28 potentially functional single-nucleotide polymorphisms (SNPs) of four RNA editing genes (ADARB1, ADAR, ADARB2 and AIMP2) in two independent TACE patient cohorts.Results: We found that ADARB1 rs1051367 and rs2253763 polymorphisms were markedly associated with the prognosis of HCC cases who received TACE in both cohorts. In HCC cells, the rs2253763 C-to-T change in ADARB1 3'-untranslated region attenuated its binding with miR-542-3p and allele-specifically elevated ADARB1 levels. Consistent with this, patients carrying the rs2253763 C allele showed reduced ADARB1 expression in cancer tissues and notably shorter survival after TACE therapy in comparison with individuals with the T allele. Ectopic ADARB1 profoundly enhanced the efficacy of oxaliplatin, one of the common TACE chemotherapeutic drugs.Discussion: Our findings highlighted the value of ADARB1 polymorphisms as prognostic markers in TACE therapy for HCC patients. Notably, our findings revealed that targeting the ADARB1 enzyme may be a promising therapeutic strategy in combination with TACE for HCC cases.Keywords: RNA editing, ADARB1, hepatocellular carcinoma, genetic polymorphism, gene expression, drug sensitivity